Narrative discourse theory between theory and practice An applied study of the voice saying in examples from the book "A dictionary of writers" - زرده, يوسف; ديّوب , هيفاء; مرعي السليمان العبدالله, عبد الرحمن (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
This research examines how narratives benefit from the linguistic model in the process of analyzing narrative speeches, identifying the mechanism by which the literary narration is made of the text, and knowing the methods of analyzing narrative discourse and the forms of its formulation, and the way in which the narration moves from the level of the story to the level of discourse, and structuralism was an appropriate input To find out the components of the narrative discourse through the Gerard Gennett model, all the way up to the narrator's positions and the functions that the discourse promoted in the narration narrations of Yakoot al-Hamwi in his book (Dictionary of Writers). To make this clear, the research presents a definition of the concept of discourse and narration with language and terminology, then mentions narrative theories and the linguistic model for the narrative discourse analysis, and then presents the Gerard Gennett model, and deals with examples from the book (Glossary of Writers) about the narrator's situations and linguistic, narrative and literary functions (voice saying) in the applied study, and finally The search ends with reading the results of the search